2000
DOI: 10.1590/s1415-47572000000100010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of double-stranded RNA on virulence of Paecilomyces fumosoroseus (Deuteromycotina: Hyphomycetes) against the silverleaf whitefly, Bemisia tabaci strain B (Homoptera: Aleyrodidae)

Abstract: Bands of double-stranded RNA (dsRNA) were detected in three out of twelve isolates of Paecilomyces fumosoroseus. Identity of these bands was confirmed by RNAse, DNAse and S1 nuclease treatments. The cure of dsRNA for one isolate (P92) was successfully carried out for a single conidium subculture. Isogenic strains, with or without dsRNA, were submitted to virulence tests against the whitefly Bemisia tabaci strain B. In contrast to findings for some phytopathogenic fungi, these dsRNA fragments did not cause hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
3
0
2
Order By: Relevance
“…Mycoviral infections can be very persistent and difficult to eliminate from their hosts (Martins et al, 1999;Romo et al, 2007). Different attempts to cure fungi from viruses have been reported, e.g., cycloheximide treatments, single conidium subculture, hyphal tip transfer, incubation at low or high temperatures (Carroll and Wickner, 1995;Romo et al, 2007;Souza-Azevedo et al, 2000), but they were not always successful. These difficulties to cure fungi from viral infections, plus the lack of simple methods for the artificial inoculation of mycoviruses, have greatly hampered progress in exploring mycovirus-host interactions (Ghabrial and Suzuki, 2009).…”
mentioning
confidence: 99%
“…Mycoviral infections can be very persistent and difficult to eliminate from their hosts (Martins et al, 1999;Romo et al, 2007). Different attempts to cure fungi from viruses have been reported, e.g., cycloheximide treatments, single conidium subculture, hyphal tip transfer, incubation at low or high temperatures (Carroll and Wickner, 1995;Romo et al, 2007;Souza-Azevedo et al, 2000), but they were not always successful. These difficulties to cure fungi from viral infections, plus the lack of simple methods for the artificial inoculation of mycoviruses, have greatly hampered progress in exploring mycovirus-host interactions (Ghabrial and Suzuki, 2009).…”
mentioning
confidence: 99%
“…Strain 3398M is only infected by TcV2 and TcV3. The size of the genomes of these three viruses is similar to that of some dsRNA elements reported in other hypocrealean entomopathogenic fungi such as M. anisopliae, M. flavoviride, B. bassiana, P. amoenoroseus, or P. fumosoroseus (Bidochka et al, 2000;Dalzoto et al, 2006;Inglis and Valadares-Inglis, 1997;Melzer and Bidochka, 1998;Souza Azevedo et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
“…Mycoviral infections can be very persistent, and difficult to eliminate from their hosts (Martins et al, 1999;Romo et al, 2007). Many attempts to cure fungi from viruses using different treatments have been reported, e.g., cycloheximide treatments, single conidium subculture, hyphal tip transfer, incubation at low or high temperatures (Carroll and Wickner, 1995;Marquez et al, 2007;Romo et al, 2007;Souza Azevedo et al, 2000), but they were not always successful. These difficulties to cure fungi from viral infections, and the lack of simple methods for the artificial inoculation of mycoviruses, have greatly hampered progress in exploring mycovirus-host interactions (Ghabrial and Suzuki, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fargues et al (2002) reported on the genetic variability among P. fumosoroseus isolates as a function of geographical and host insect origins. Azevedo et al (2000b) identified isolates with double stranded RNA, but they exhibited no differences in virulence from isolates with single stranded RNA. Cantone and Vandenberg (1998) considered that DNA fingerprinting with RAPD-PCR could be useful in tracking the fate of fungi released into the environment as biological control agents.…”
Section: Genetic and Molecular Studiesmentioning
confidence: 96%